An introduction to the sociology of religion : classical and contemporary perspectives - Furseth, Inger; Repstad, Pål. (Aldershot, England ; Burlington, VT : Ashgate, 2006)
"An Introduction to the Sociology of Religion provides an overview of sociological theories of contemporary religious life. Some chapters are organized according to topic. Others offer brief presentations of classical and contemporary sociologists from Karl Marx to Zygmunt Bauman and their perspectives on social life, including religion. Throughout the book, illustrations and examples are taken from several religious traditions."--BOOK JACKET.
Table of contents
Includes bibliographical references (p. [209]-234) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Religion and sociology; Electronic books